Variabilidad genética de Phytelephas macrocarpa (Arecaceae) mediante marcadores ISSR (Inter Simple Sequence Repeat) en seis poblaciones naturales de la región San Martín - Cruz Chavarry, Wheeler José (2019)
The population genetic variability of the Phytelephas macrocarpa “Yarina” was analyzed using ISSR (Inter simple sequence repeat) molecular markers in 6 natural populations of the San Martín region (Palestine, Caynarachi, Andiviela, Picota, Pachiza and Tocache). A total of 72 samples (12 samples from each population) were analyzed with three ISSR markers: GAG(CAA)5, CAG5 and CAA5. The ISSR markers were polymorphic, achieving a total of 60 polymorphic bands (31 bands were diagnostic). The ISSR markers were useful for the construction of the total genotype, with CAA5 being the one with the most gender bands (21 in total). The results of the correspondence factor analysis (AFC) and the dendogram estimated by the Neighbor-Joining method associate the populations studied in 3 well-differentiated groups, showing us a well-structured genetic structuring and differentiation between them. These groups were: 1) Palestine, 2) Tocache and 3) Caynarachi, Andiviela, Picota and Pachiza. On the other hand, the index of fixation, genetic distance and genetic flow showed a strong association between the populations of Pachiza and Tocache, while Caynarachi and Tocache, a considerable distance. Genetic distances and geographical distances have a weak positive linear correlation (r = 0,23), this due to the geographical diversity of the San Martín region (natural corridors, natural barriers, altitudinal floors, etc.).